PEMANFAATAN LIMBAH PRODUKSI TAHU SEBAGAI PUPUK ORGANIK CAIR DESA SUKASUKUR - Rustiana, Nova Nur Rustiana; Seni Sri Wahyuni, Seni Sri Wahyuni; Tanto Muhammad Ridho, Tanto Muhammad Ridho; Alya Alfinati, Alya Alfinati; Rama Rizkya Rahman Prasyam, Rama Rizkya Rahman Prasyam; Asri Ulannisa Azzahra, Asri Ulannisa Azzahra; Tineu Indrianeu, Tineu Indrianeu (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The program was conducted to study the utilization of liquid waste from tofu industries in Sukasukur Village as the main raw material for producing liquid organic fertilizer. This activity was designed through a socialization program with the Munjul Women Farmers' Community (KWT) in Sukasukur Village, focusing on enhancing the community's understanding of the impacts and importance of managing tofu liquid waste as a contribution to preserving the surrounding environment. The results showed that KWT members began to recognize the impacts of the waste and were able to independently and sustainably practice tofu liquid waste management techniques using a simple fermentation method.